Professional Standards and Recognition for UK Personal Tutoring and Advising - Walker, Ben W. (Frontiers in Education, 2020)
The Higher Education and Research Act established both a regulatory framework and the Teaching Excellence Framework with associated metrics for student retention, progression and employability in the UK. As a key site in meeting these requirements, the significance of personal tutoring is clear. Despite this, according to existing institutional research, there is a need for developmental support, greater clarification on the requisite competencies, and adequate recognition for those undertaking this challenging role. Moreover, arguably compounding these concerns is the lack of distinct professional standards for personal tutoring and advising against which to measure effective practice, only recently addressed by the publication of The UKAT Professional Framework for Advising and Tutoring. Through a review of the literature supported by findings from a survey of practitioners, this paper discusses the need for such standards, and the skills and competencies populating them. Additionally, the usefulness of pre-existing standards pertinent to tutoring work (such as the UK Professional Standards Framework for Teaching and Supporting Learning in HE) are evaluated and the value and recognition with which personal tutoring standards could be associated are advanced. The survey supported the need for specific standards – represented by the UKAT framework - as evident from the literature. Justifications provided for both this and the opposing view are examined. Clarity for both individual practitioners and institutions was stipulated along with meaningful recognition and reward for this work which is considered highly important and yet ‘invisible’. The participants and literature reviewed identify relevant content along with illuminating the debate about the relationships between personal tutoring, teaching and professional advising roles. Valuable analysis of standards, recognition and reward also emerged. This is considered by discussing the connection between standards and changes to practice, responses to policy developments and the purpose of ‘standards’ in comparison to ‘guidance’. The paper proposes that the recent introduction and use of a bespoke framework is a necessary response to alleviate some of the current tensions which beset personal tutoring and advising in higher education.